Football Associations of Malaysia: the case study on managing performance for the competition department in F.A.M / Ahmad Roziman Ahmad Murad - Ahmad Murad, Ahmad Roziman (Faculty of Business and Management, 2010)
Performance management includes activities to ensure that goals are consistently being met in an effective and efficient manner. Performance management can focus on performance of the organization, a department, processes to build a product or service, employees. Information in this topic will give you some sense of the overall activities involved in performance management.